The contribution of school feeding programs to children’s energy and nutrient intakes in six selected departments of Benin - Tossou, Mahounakpon W; Ainin, Abiola; Ayede, Adeline O. A.; Soetonve, Emmanuella N.; Turimubumwe, Isaac; Hevinouyoue, Augustine; Boyiako, Bernadette; Achamou, Mourichide; Fanou-Fogny, Nadia (World Nutrition, 2025)
Benin has implemented a school feeding program to promote children’s education and enhance the quality of food and nutrition provided to them. To assess the nutritional value of school meals served by government canteens, a cross-sectional study was conducted from November to December 2020 in the departments (districts) of Atacora, Collines, Couffo, Mono, Ouémé, and Plateau among 1502 school-aged children in 167 public primary schools with and without a government canteen. The direct food weighing method and the 24-hour dietary recall questionnaire were used to assess the nutritional content (energy, iron, and vitamins A and C) of foods and the dietary diversity of the children’s diets. Data were analyzed using STATA software version 16.0. The results showed an average energy supply of 669 (SD = 316.3) Kcal, with 57% of schools covering at least 1/3 of the children’s energy needs. The nutrient content of the food offered was found to be low compared to daily intake recommendations (iron: 15.9%, vitamin A: 17.7%, and vitamin C: 12.8%). With regard to dietary diversity over the entire day, there was no significant difference between schools with and without a government canteen. To reduce the micronutrient deficiencies among these children, setting up a school garden could be an important initiative to make fresh fruits and vegetables available for use in school meals.